Path correlation and bayesian analysis on popping expansion components in popcorn hybrids - De Oliveira, Gustavo Hugo Ferreira; Pelegrini, Gabriela [UNESP]; De Oliveira, Tâmara Rebecca Albuquerque; Carvalho, Maisa Nascimento; Môro, Gustavo Vitti [UNESP] (Universidad Nacional de Colombia, 2020)
Knowing the cause and effect among two or more traits can help to increase the selection accuracy of superior genotypes. The main objective of this study was to evaluate the cause and effect relationship between expansion volume and kernel size in popcorn hybrids using path analysis and Bayesian network. A total of 41 popcorn hybrids were evaluated through a randomized complete block design (RCBD) with two replicates in the city of Jaboticabal, Brazil. The assessed traits were grain length (GL), grain thickness (GT), grain width (GW), caryopsis roundness index (CRI), mass of 50 grains (MG), and expansion volume (EV). Measurements were performed on individual grains, using three 50-grain samples from each plot. Pearson’s correlation coefficient, path analysis and Bayesian network were estimated. A negative correlation was detected among EV and the traits, except for GT. Path analysis indicated that MG has a direct and positive effect on EV and the negative correlation observed is mainly due to the indirect effects by GL and GT. Bayesian networks did not detect a direct association between kernel size and expansion volume while indicating that GT is the only trait that can affect popcorn flake size.
Correlación de ruta y análisis bayesiano sobre componentes de expansión en híbridos de maíz pipoca
Keywords: Bayesian networks; Correlation; Direct and indirect effect; Zea mays l. var. everta